Anodic Oxidation of Caffeine and Theophylline in Glacial Acetic Acid. Issue 3 (7th March 2016) - Quintanilla, Gloria; Usarralde, Ángela; Pérez, Iván; Gargiulo, Maria L.; Yakupoglu, Gökce; Martín, Avelino; Barba, Fructuoso
Abstract: The anodic oxidation of caffeine and theophylline has been carried out at a controlled potential in a one compartment cell using glassy‐carbon as the anode, platinum as the cathode and glacial acetic acid/sodium acetate as solvent‐supporting‐electrolyte (SSE). The oxidation of caffeine yields 1, 3, 8‐trimethyl‐1, 3, 6, 8‐tetrazaspiro[4.4]nonane‐2, 4, 7, 9‐tetrone and (4‐acetoxy‐1, 3, 7‐trimethyl‐2, 6, 8‐trioxo‐9H‐purin‐5‐yl) acetate . Despite of the different structure, the oxidation of theophylline leads only to the same spiro compound 1, 3, 8‐trimethyl‐1, 3, 6, 8‐tetrazaspiro[4.4]nonane‐2, 4, 7, 9‐tetrone as in the case of caffeine. The structure of both compounds is described and the reaction mechanism is discussed. Abstract : The anodic oxidation of caffeine in AcOH/AcNa at a controlled potential leads to 1, 3, 8‐trimethyl‐1, 3, 6, 8‐tetrazaspiro[4.4]nonane‐2, 4, 7, 9‐tetrone and (4‐acetoxy‐1, 3, 7‐trimethyl‐2, 6, 8‐trioxo‐9H‐purin‐5‐yl) acetate, whereas theophilline yields exclusivelly the same spiro compound.